Integrating online dynamic assessment and active learning to mitigate speaking anxiety in EFL contexts: A conceptual framework - Ikma Wati; Anisa Nurjanah; Zhyldyz Tunguchbaevna Takenova; Dinara Asanova (Researcher and Lecturer Society, 2025)
Speaking anxiety remains a persistent challenge for learners of English as a Foreign Language (EFL), particularly in online learning environments where limited interaction, delayed feedback, and concerns about performance visibility may intensify emotional discomfort. Such anxiety often leads to reduced participation, diminished confidence, and slower speaking development. While previous research has examined Online Dynamic Assessment (ODA) and Active Learning (AL) independently, limited attention has been paid to their pedagogical integration as a unified framework for reducing anxiety. Drawing on sociocultural theory and recent empirical studies published between 2021 and 2025, this conceptual paper proposes an integrative ODA-AL framework designed to address both the cognitive and affective dimensions of EFL speaking. ODA emphasizes mediated feedback and scaffolding to support learners’ developmental potential, while AL promotes engagement, enjoyment, and social interaction through participatory speaking activities. The proposed framework conceptualizes speaking anxiety reduction as an outcome of pedagogical design that aligns assessment with instruction and emotional support. This study contributes to theoretical discussions on affective variables in language education and offers practical implications for EFL instructors. Directions for future empirical research are also discussed.